KUALITAS PELAYANAN PENGADUAN PENGGUNA JASA PDAM KOTA SURABAYA (Studi tentang tingkat Responsivitas dan Akuntabilitas PDAM dalam memberikan pelayanan pengaduan pelanggan air kotor/bau) - Fatmala, Fikri (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
Quality Services User of Service User Pdam City Surabaya (Study on PDAM Responsiveness and Accountability in providing customer service of dirty/smelly water). Settlement in Surabaya city is one of clean water prone area. So far the distribution of clean water is done through home connection obtained from pdam Surya Sembada in Surabaya city, but the service obtained stiil not in accordance with service standard. This study aims to how resposiveness an akuntability PDAM Surabaya city in providing services. The method used in this research is qualitative descriptive method whit focus of public service covering, service procedure, completion time, competence of service providr officer. Research results can be seen that customer complaints service water distribution system that has been implemented well enough about the procedures service, facilities and infrasructure, the competence of serviceprovider. But at this yime the process of workmanship provided by the officer has not been in accordance whit waht is set and the officer so far only responds to all customer complaints but not acted upon. Â Keyword : service, responsiveness and accountability